Compared growth, mineral nutrition and aechnological characteristics in Sorghum - Castro, Paulo R. C.; Appezzato, Beatriz; Lucchesi, Antonio A.; Cesar, Marco A. A.; R. Dechen, Antonio; Elias, Maria (Pesquisa Agropecuaria Brasileira, 2014)
A sorghum (Sorghum bicolor (L.) Moench) field experiment was carried out in the experimental area of Botany Department of ESALQ/USP, in Piracicaba, SP, Brazil, during 1983/1984. The growth of BR 501, BR 503. BR 505 and CMS x S 623 cultivars of sorghum was compared through growth analysis; the concentration of macronutrients in leaves was determined, and technological analysis of stalks during maturity period was realized. Cultivar BR 503 showed highest biomass production, presenting highest values of dry matter production DMP), net assimilation rate (NAR), and relative growth rate (RGR); cultivar CMS x S 623 presented lowest biomass production. The order of nitrogen concentration decreased on leaves of CMS x S 623 > BR 503> BR 505> BR 501 cultivars. The concentration of P was higher on BR 501 and BR 505 cultivars than in CMS x S 623 and BR 503 cultivars. The order of potassium concentration decrease on leaves was BR 505 > BR 501 > BR 503 > CMS x S 623 sorghum cultivars. Cultivars BR 505 and BR 501 showed best technological characteristics for alcohol production.